Phylogeny of North American Tolypella (Charophyceae, Charophyta) based on plastid DNA sequences with a description of Tolypella ramosissima sp. nov. Issue 5 (16th August 2014) - Pérez, William; Hall, John D.; McCourt, Richard M.; Karol, Kenneth G.; Vis, M.
<x xml:space="preserve">Abstract</x> Characeae (Charophyceae, Charophyta) contains two tribes with six genera: tribe Chareae with four genera and tribe Nitelleae, which includes Tolypella and Nitella. This paper uses molecular and morphological data to elucidate the phylogeny of Tolypella species in North America. In the most comprehensive taxonomic treatment of Characeae, 16 Tolypella species worldwide were subsumed into two species, T. intricata and T. nidifica, in two sections, Rothia and Tolypella respectively. It was further suggested that Tolypella might be a derived group within Nitella. In this investigation into species diversity and relationships in North American Tolypella, sequence data from the plastid genes atpB, psbC, and rbcL were assembled for a broad range of charophycean and land plant taxa. Molecular data were used in conjunction with morphology to test monophyly of the genus and species within it. Phylogenetic analyses of the sequence data showed that Characeae is monophyletic but that Nitelleae is paraphyletic with Tolypella sister to a monophyletic Nitella + Chareae. The results also supported the monophyly of Tolypella and the sections Rothia and Tolypella. Morphologically defined species were supported as clades with little or no DNA sequence differences. In addition, molecular data revealed several lineages and a new species (T. ramosissima sp. nov.), which suggests greater species diversity in Tolypella than previously recognized.